Striking a Better Balance : Volume 1. The World Bank Group and Extractive Industries - World Bank (World Bank, Washington, DC, 2014)
In July 2001, the extractive industries review (EIR) was initiated with the appointment of Dr. Emil Salim, former Minister of the Environment for Indonesia, as eminent person to the review. The EIR was designed to engage all stakeholders-governments, nongovernmental organizations (NGOs), indigenous peoples' organizations, affected communities and community-based organizations, labor unions, industry, academia, international organizations, and the World Bank Group (WBG) itself-in a dialogue. The basic question addressed was, can extractive industries projects be compatible with the WBG's goals of sustainable development and poverty reduction? The EIR believes that there is still a role for the WBG in the oil, gas, and mining sectors-but only if its interventions allow EI to contribute to poverty alleviation through sustainable development. And that can only happen when the right conditions are in place. This report makes major recommendations on how to restore the balance in the WBG - promote pro-poor public and corporate governance in the EI, strengthen environmental and social components of WBG interventions in these industries, respect human rights, and rebalance WBG institutional priorities. These recommendations have as the ultimate goal: to lift up civil society so it is balanced in the triangle of partnership between governments, business, and civil society; to raise social and environmental considerations so they are balanced with economic considerations in efforts at poverty alleviation through sustainable development; and to strive for a human-rights-based development that balances the material and the spiritual goals of life.